Conocimiento y práctica de medidas preventivas sobre enfermedad diarreica aguda en madres con menores de 5 años del asentamiento humano Munich Iquitos 2022 - Malaverry Tangoa, Filida Carmin (2023)
The objective was to determine the relationship between the knowledge and practice of preventive measures on Acute Diarrheal Disease in mothers with children under 5 years of age in the Human Settlement Munich Iquitos 2022, the type of study was Quantitative, and with a non-experimental design, of a correlational type; The population was made up of 50 mothers of children under 5 years of age cared for in the IPRESS I-2 January 1st of the Munich Human Settlement in Iquitos. The techniques that were used were the interview, observation and home visit; the instruments were the knowledge questionnaire on Acute Diarrheal Disease (Validity 95.88% and Reliability 83.90%), and the checklist of practices on preventive measures of Acute Diarrheal Disease (Valdez 98.75% and Reliability 96.00 %). The study determined a predominance of bad knowledge with 60.0%, followed by regular knowledge with 30.0% and good knowledge with 10.0%; in the practices of preventive measures on Acute Diarrheal Disease, bad practices predominated with 80.0% followed by good practices with 20.0%, Chi square X2 = 29.167 was found; for p = 0.000 < 0.05, df = 2 and 95% confidence level. The work concluded that there is a relationship between knowledge and practices of preventive measures on Acute Diarrheal Disease in mothers with children under 5 years of age in the Human Settlement Munich Iquitos 2022.